The life of Abu Hafs al-Nasafi and the source study analysis of the work “al-Taysir fit-tafsir”. - Abdulkhodiyev Dovudkhon (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
This article analyzes the life and scientific heritage of the 12th-century encyclopedic scholar Abu Hafs al-Nasafi and his work “al-Taysir fit-tafsir” from a source study perspective. The research highlights the author’s unique methods in writing tafsir, specifically the method of interpreting verses with other verses and techniques for defending the Ahli Sunna creed. Additionally, the significance of the work in preserving the traditions of the Maturidite school of kalam and the classification of sources used therein are presented.